2008
DOI: 10.1002/dvdy.21626
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases 1 and 2 are expressed at distinct stages of neuro‐glial development

Abstract: The deacetylation of histone proteins, catalyzed by histone deacetylases (HDACs), is a common epigenetic modification of chromatin, associated with gene silencing. Although HDAC inhibitors are used clinically to treat nervous system disorders, such as epilepsy, very little is known about the expression pattern of the HDACs in the central nervous system. Identifying the cell types and developmental stages that express HDAC1 and HDAC2 within the brain is important for determining the therapeutic mode of action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 55 publications
7
141
1
3
Order By: Relevance
“…HDAC1 and HDAC2 expression during brain development has been extensively studied and show relatively contrasting expression patterns throughout the central nervous system. HDAC1 is highly expressed in glia, whereas HDAC2 shows high expression in mature neurons, however, both are expressed in neuronal stem cells/progenitors during embryonic development (13). HDAC1 loxP/loxP ; GFAP-Cre and HDAC2 loxP/loxP ; GFAP-Cre mice were born at normal Mendelian ratios and showed normal brain histoarchitecture, behavior, motor skills, and lifespan (supporting information (SI) Fig.…”
Section: Resultsmentioning
confidence: 98%
“…HDAC1 and HDAC2 expression during brain development has been extensively studied and show relatively contrasting expression patterns throughout the central nervous system. HDAC1 is highly expressed in glia, whereas HDAC2 shows high expression in mature neurons, however, both are expressed in neuronal stem cells/progenitors during embryonic development (13). HDAC1 loxP/loxP ; GFAP-Cre and HDAC2 loxP/loxP ; GFAP-Cre mice were born at normal Mendelian ratios and showed normal brain histoarchitecture, behavior, motor skills, and lifespan (supporting information (SI) Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To better understand the molecular mechanisms through which E 2 might increase histone H3 acetylation, we measured protein and mRNA expression of the HDAC enzymes 1 and 2 (HDAC1 and HDAC2) in dorsal hippocampus after IH E 2 infusion. Both HDACs are expressed in adult mouse hippocampus, where HDAC1 is expressed in glia and neural progenitor cells, and HDAC2 is expressed in neurons and neural progenitors (16). HDAC1 regulates cell proliferation and differentiation and is neuroprotective in mouse forebrain (17).…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse system MacDonald and Roskams reported that both HDAC1 and HDAC2 are expressed in neural progenitor and stem cells (MacDonald and Roskams, 2008). Strikingly, upon lineage specification into either glial cells or neuroblasts and post-mitotic neurons, HDAC1 and HDAC2 are found to be mutually exclusive expressed.…”
Section: Hdac1 and Hdac2 In Heart Developmentmentioning
confidence: 99%